Assessment of Single‐Cycle M‐Protein Mutated Vesicular Stomatitis Virus as a Safe and Immunogenic Mucosal Vaccine Platform for SARS‐CoV‐2 Immunogen Delivery - En Zhang; Yong Ke; Weihong Ran; Yu Zhang; Ruihang Li; Xinkui Fang; Lei Wang; Baohong Zhang; Tao Sun (Advanced Science)
Abstract The goal of the next‐generation COVID‐19 vaccine is to provide rapid respiratory tract protection with a single dose. Circulating antibodies do not protect the olfactory mucosa from viral infection, necessitating localized mucosal immunization. Live attenuated vesicular stomatitis virus (VSVMT)‐based COVID‐19 vaccines effectively stimulate mucosal immunity in animals, though safety concerns remain, particularly in immunocompromised populations. A viral vector capable of single‐cycle replication may face less stringent regulatory requirements. A replication‐defective VSVMT is developed with its G protein replaced by a SARS‐CoV‐2 spike protein (S) mutant, where residues K986 and V987 are substituted by prolines (S2P). This studies show that single‐cycle VSVMT encoding Omicron subvariant S2P (VSVMT‐S2P) is safe in both healthy and immunocompromised animals treated with cyclophosphamide (CP). Significant antibody and T‐cell responses against the spike protein are observed in VSVMT‐S2P vaccinated healthy animals. Intramuscular VSVMT‐S2P administration induces neutralizing antibody responses comparable to those from replication‐competent VSVMT‐S. In immunocompromised animals, lower and delayed immune responses are observed. Thus, single‐cycle M‐protein mutated VSV offers a safe and effective platform for SARS‐CoV‐2 immunogen delivery. Remarkably, replication‐competent VSVMT‐S caused no pathogenicity and elicited potent mucosal immunity via intranasal administration, highlighting its potential as a mucosal COVID‐19 vaccine.